2023
DOI: 10.5812/ans-134291
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Head Trauma in Iran: A Systematic Review and Meta-analysis

Abstract: Context: Head trauma (HT) is one of the most important types of traumata that has a high prevalence and may occur in different age groups, ranging from infants to the elderly. Objectives: Considering the importance of the prevalence of all types of traumata, especially HT, this study was conducted to measure the prevalence of HT in Iran by systematic review and meta-analysis. Methods: The present systematic review and meta-analysis was conducted according to the PARISMA checklist to assess the prevalence of HT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Other studies have focused on different age groups. For instance, Sadeghi et al reported a prevalence of trauma at 26.2% (95% CI [14.4 -29.2]) (22), and a meta-analysis by Maleki et al in Iran found the prevalence of traumatic spinal cord injury (TSCI) to be 3 per 10,000 people, with a mean mortality rate of 3.9% (23).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have focused on different age groups. For instance, Sadeghi et al reported a prevalence of trauma at 26.2% (95% CI [14.4 -29.2]) (22), and a meta-analysis by Maleki et al in Iran found the prevalence of traumatic spinal cord injury (TSCI) to be 3 per 10,000 people, with a mean mortality rate of 3.9% (23).…”
Section: Discussionmentioning
confidence: 99%